Institutional and national challenges of teacher education in the context of the COVID-19 pandemic - Dorozh, Iryna; Bielykh, Oksana; Blyznyuk, Lyudmyla; Tovkun, Lidiia; Kotsur, Nadiia (EAAR - Editorial Authors and Associated Researchers, 2021)
The purpose of the study is to establish the pattern of institutional and national challenges for teacher education in the context of the COVID-19 pandemic, by conducting regression analysis and research of regulations of the world, to identify challenges for teacher education and the ability to provide quality education in the context of distance learning. Research methods: systematization; comparative analysis; generalization; regression analysis. Results. After conducting a regression analysis, it was found that the value of the coefficient of determination shows that the regression model by 60% reflects the direct dependence of the availability of emergency distance education in 30 countries, based on the results of access to personal computers among students and the current cost of education. It has been established that countries such as Denmark, Switzerland, Austria, Norway and Luxembourg have a favorable climate for emergency distance education.
Keywords: Institutional and national challenges; Teacher education; Distance education; Educational institutions; COVID-19 pandemic